Sorghum bicolor INDETERMINATE1 is a conserved primary regulator of flowering - De Riseis, Samuel; Chen, Junping; Xin, Zhanguo; Harmon, Frank G. (Frontiers in Plant Science, 2023)
A fundamental developmental switch for plants is transition from vegetative to floral growth, which integrates external and internal signals. Indeterminate (Id1) family proteins are zinc finger transcription factors that activate flowering in grasses regardless of photoperiod. Mutations in maize Id1 and rice Id1 (RID1) cause very late flowering. RID1 promotes expression of the flowering activator genes Early Heading Date1 (Ehd1) and Heading date 1 (Hd1), a rice homolog of CONSTANS (CO). Mapping of two recessive late flowering mutants from a pedigreed sorghum EMS mutant library identified two distinct mutations in the Sorghum bicolor Id1 (SbId1) homolog, mutant alleles named sbid1-1 and sbid1-2. The weaker sbid1-1 allele caused a 35 day delay in reaching boot stage in the field, but its effect was limited to 6 days under greenhouse conditions. The strong sbid1-2 allele delayed boot stage by more than 60 days in the field and under greenhouse conditions. When sbid1-1 and sbid1-2 were combined, the delayed flowering phenotype remained and resembled that of sbid1-2, confirming late flowering was due to loss of SbId1 function. Evaluation of major flowering time regulatory gene expression in sbid1-2 showed that Id1 is needed for expression of floral activators, like SbCO and SbCN8, and repressors, like SbPRR37 and SbGhd7. These results demonstrate a conserved role for SbID1 in promotion of flowering in sorghum, where it appears to be critical to allow expression of most major flowering regulatory genes.